Distribution of a giant panda population influenced by land cover. Issue 6 (1st May 2018) - Zhang, Yuke; Wu, Yongjie; Zhang, Qiongyue; Ran, Jianghong; Price, Megan
ABSTRACT: The distribution of species and their causes are key questions for population ecology and conservation. Giant pandas ( Ailuropoda melanoleuca ) in the Daxiangling Mountains, China are part of an isolated population on the edge of the species' range and little is known regarding their distribution. Based on land cover, topography, human disturbance, and panda occurrence data in 2 national giant panda surveys, we used a species distribution model (i.e., MaxEnt) to simulate habitat distribution changes of the local panda population between 2001 and 2012. During this time the area of coniferous forest and broadleaf forest increased by 16.4% and 5.8%, respectively, whereas the shrub‐grass and agricultural land decreased by 45.1% and 4.0%, respectively. Panda habitat increased from 460.3 km 2 in 2001 to 591.3 km 2 in 2012. Panda distribution in the Daxiangling Mountains was primarily influenced by land cover, topography, and human activities. Our study demonstrates that habitat recovery in the Daxiangling Mountains created a favorable environment for the local panda population; thus, the boundary of panda reserves should be adjustable based on their use of the landscape. Future research should focus on dispersal and distribution of pandas to better understand their land use for effective conservation. © 2018 The Wildlife Society. Abstract : Land‐cover change monitoring and species distribution modeling identified changes of key land‐cover types (e.g., increasing forest, reduced agriculture land) that have led to an increase in giant panda habitat in the Daxiangling Mountains, China. Conservation management should incorporate forest monitoring and land‐use planning to improve the quality and connection of habitat for panda dispersal.